INTER-FAITH BELIEVER’S CONFLICTS AND ITS SOLUTIONS IN NORTH SUMATRA INDONESIA - Arifinsyah Arifinsyah (Studia Sosia Religia, 2020)
AbstractThe aim of this study is to find out the root of the conflict and its solution proposed by the religious leaders to maintain the harmony among religious believers. After conducting a qualitative research, the results show that the conflict in this region is more dominant coming from the economic resources, not because of religious teachings. Besides, they are also caused by the behaviour of the believers concerning to religious cultural identity but they are relatively small. The solutions given  by the leaders indicate that (1) building up the commitment of togetherness among the leaders, (2) the support of the public leaders in mediating the conflicting believers, (3) the multiple  role of the leaders in socializing the universal values of the religious teaching and the local wisdom, and (4) doing inter-faith and inter-ethnic dialogues among the believers honestly, openly, respectively. By doing these, the excellence and the national harmony in north Sumatera will come true.Keywords: inter-faith believer’s conflicts, national harmonyAbstrakTujuan dari penelitian ini adalah untuk mengetahui akar dari konflik dan solusi yang diajukan oleh para pemuka agama untuk menjaga kerukunan umat beragama. Setelah dilakukan penelitian kualitatif, didapatkan hasil bahwa konflik di wilayah ini lebih dominan bersumber dari sumber daya ekonomi, bukan karena ajaran agama. Selain itu, juga disebabkan oleh perilaku pemeluk agama yang terkait dengan identitas budaya agama namun relatif kecil. Solusi yang diberikan oleh pemimpin menunjukkan bahwa (1) membangun komitmen kebersamaan antar pemimpin, (2) dukungan pemimpin masyarakat dalam memediasi konflik pemeluk agama, (3) peran ganda pemimpin dalam mensosialisasikan nilai-nilai universal. tentang ajaran agama dan kearifan lokal, dan (4) melakukan dialog antaragama dan antaretnis antar umat beriman secara jujur, terbuka, masing-masing. Dengan demikian akan terwujud keunggulan dan kerukunan bangsa di Sumatera Utara.Kata Kunci : Konflik Antar Umat Beragama, Kerukunan Bangsa